2021
DOI: 10.1051/shsconf/20219701042
|View full text |Cite
|
Sign up to set email alerts
|

Students’ attitude to e-learning

Abstract: In the context of the Covid-19 pandemic, the relevance of the transition to remote forms of training has increased not only for part-time students, but also for full-time ones. Online learning, based on the use of various electronic educational platforms, differs significantly from the traditional system and completely changes the entire educational process, including the forms of knowledge acquisition, control and assessment. ELearning has many advantages, but it can only be considered as an addition to tradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It is suggested that necessary technical changes must be made in online learning design to facilitate peer interaction, support and socialisation in the online learning environment (Hasan & Khan, 2020). A smooth process of communication and interaction will hinder students' frustration and boost their belief in online learning (Mukhametshin et al, 2021).…”
Section: Can Text My Teacher At Any Time To Ask a Question (Student 7)mentioning
confidence: 99%
“…It is suggested that necessary technical changes must be made in online learning design to facilitate peer interaction, support and socialisation in the online learning environment (Hasan & Khan, 2020). A smooth process of communication and interaction will hinder students' frustration and boost their belief in online learning (Mukhametshin et al, 2021).…”
Section: Can Text My Teacher At Any Time To Ask a Question (Student 7)mentioning
confidence: 99%
“…The first one is to evaluate the success of the e-learning service and the second aspect assesses the impact of e-learning services on learning and academic performance of students. Mukhametshin et al (2021) examined the various aspects of the remote leaning system as an effective tool to manage the current demand posed by the pandemic towards educational institutions [38]. The results indicated the negative impressions of the students due to unstable internet connection along with the difficulty faced by the students while preparing for the assignment given by the teachers without much explanation.…”
Section: F Effectiveness Of the E-learningmentioning
confidence: 99%
“…Some students who engaged in E-learning have better academic performance and thus they have a positive attitude towards E-learning [5] and are satisfied with it [6]. Others have negative impressions and assessments of E-learning [7], and thus they are unsatisfied with E-learning [8].…”
Section: Introductionmentioning
confidence: 99%